Greed as Organizational DNA: External Auditor's Perceptions - Aulia Zahra Putriani; Titik Agus Setiyaningsih (Journal of Accounting Science, 2026)
General Background: Organisational misconduct is not only caused by individual errors, but also by patterns of behaviour that develop internally. Greed is one such pattern and gradually shapes the organisation's mindset and decision-making. Specific Background: During audits, external auditors often encounter clients who exhibit repetitive decision-making patterns and ingrained organisational routines. From the auditor's perspective, these patterns indicate greed that has been internalised in the organisation's systems and operational practices. This condition shapes the character of the organisation, reflected in shared norms, values, and procedural frameworks that guide decision-making processes, information flows, and managerial motivation. Knowledge Gap: Several studies using quantitative or qualitative approaches have addressed greed. However, studies linking greed to the concept of organisational DNA and viewing it from the perspective of external auditors as a phenomenological lens are still rare. Method: To explore how auditors understand greed in organisational DNA, this study adopts a qualitative approach and Alfred Schutz's social phenomenology as its methodological framework. Results: The results show that auditors often identify patterns of greed from interactions with clients, financial reports, decision-making processes, and management responses. This greed develops from repeated decisions and justifications until it eventually becomes part of the client's organisational DNA. Novelty: This study uses the auditor's experience as a lens to understand greed as part of the client's organisational DNA and combines the Organisational DNA framework with Schutz's phenomenology. Implications: These findings help auditors and regulators become more sensitive to client behaviour patterns and encourage audits that focus not only on numbers, but also on the behaviour, culture, and character of the organisation.